Inhibitory Effect of Herbal Remedy PERVIVO and Anti-Inflammatory Drug Sulindac on L-1 Sarcoma Tumor Growth and Tumor Angiogenesis in Balb/c Mice - P. Skopiński; B. J. Bałan; J. Kocik; R. Zdanowski; S. Lewicki; M. Niemcewicz; K. Gawrychowski; E. Skopińska-Różewska; W. Stankiewicz (Hindawi Limited, 2013)
Anticancer activity of many herbs was observed for hundreds of years. They act as modifiers of biologic response, and their effectiveness may be increased by combining multiple herbal extracts . PERVIVO, traditional digestive herbal remedy, contains some of them, and we previously described its antiangiogenic activity. Numerous studies documented anticancer effects of nonsteroidal anti-inflammatory drugs. We were the first to show that sulindac and its metabolites inhibit angiogenesis. In the present paper the combined in vivo effect of multicomponent herbal remedy PERVIVO and nonsteroidal anti-inflammatory drug sulindac on tumor growth, tumor angiogenesis, and tumor volume in Balb/c mice was studied. These effects were checked after grafting cells collected from syngeneic sarcoma L-1 tumors into mice skin. The strongest inhibitory effect was observed in experimental groups treated with PERVIVO and sulindac together. The results of our investigation showed that combined effect of examined drugs may be the best way to get the strongest antiangiogenic and antitumor effect.